Prevalence and Postdischarge Outcomes Associated with Frailty in Medical Inpatients: Impact of Different Frailty Definitions. Issue 7 (20th March 2019) - McAlister, Finlay A; Lin, Mu; Bakal, Jeffrey A
Abstract : We compared prevalence estimates and prognostication if frailty were defined using the face‐to‐face Clinical Frailty Scale (CFS) or the administrative‐data‐derived Hospital Frailty Risk Score (HFRS). We evaluated 489 adults from a prospective cohort study of medical patients being discharged back to the community; 276 (56%) were deemed frail (214 [44%] on the HFRS and 161 [33%] on the CFS), but only 99 (20%) met both frailty definitions (kappa 0.24, 95% CI 0.16‐0.33). Patients classified as frail on the CFS exhibited significantly higher 30‐day readmission/ death rates, 19% versus 10% for those not frail (aOR [adjusted odds ratio] 2.53, 95% CI 1.40‐4.57) and 21% versus 6% for those aged >65 years (aOR 4.31, 95% CI 1.80‐10.31). Patients with HFRS‐defined frailty exhibited higher 30‐day readmission/death rates that were not statistically significant (16% vs 11%, aOR 1.62 [95% CI 0.95‐2.75] in all adults and 14% vs 11%, aOR 1.24 [95% CI 0.58‐2.83] in those aged >65 years).